2019
DOI: 10.1080/19463014.2019.1628792
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical translanguaging and the construction of science knowledge in a multilingual South African classroom: challenging monoglossic/post-colonial orthodoxies

Abstract: The majority of learners in South African schools are African language speakers, yet the dominance of English in the political economy has meant that schools choose to switch to English medium instruction by Grade 4, before learners have the necessary English proficiency to access the curriculum, with negative effects on learning. This paper outlines South Africa's long engagement with such issues and documents the translanguaging practices of a teacher who breaks the post-colonial monolingual ideologies preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 27 publications
2
19
0
2
Order By: Relevance
“…For teachers to accept such practices (marking a student down for spelling) can be visible as a vital evil and a deviation from a monolingual ideal and a source of conflict and tension" [63,64,65]. Contrary to this view, Sobahle [52] argues that "it has also been established that students have both social and linguistic reasons for code-switching".…”
Section: Discussionmentioning
confidence: 99%
“…For teachers to accept such practices (marking a student down for spelling) can be visible as a vital evil and a deviation from a monolingual ideal and a source of conflict and tension" [63,64,65]. Contrary to this view, Sobahle [52] argues that "it has also been established that students have both social and linguistic reasons for code-switching".…”
Section: Discussionmentioning
confidence: 99%
“…As a pedagogical approach, translanguaging underscores the flexibility of multilingualism, considering the use of racialized, dynamic, and fluid language practices as valuable for their own sake and for the purpose of expanding students' semiotic repertoires and facilitating content-area learning. Some studies have highlighted that translanguaging pedagogies leverage students' familiar language practices to access new practices in the language of instruction and those valued within particular disciplines (e.g., Probyn, 2019). For example, Poza (2018) found that 5th-grade students' translanguaging practices facilitated the development of numerous skills central to those valued in science learning, including the use of discipline-specific vocabulary and visual supports to navigate complex texts, as well as skills surrounding the categorization of objects.…”
Section: Translanguagingmentioning
confidence: 99%
“…Current studies in EAC in the South African context have focused mainly on science and mathematics teaching, such as Msimanga et al (2017), Msimanga and Erduran (2018), and Setati (2001). There is, however, an expanse of research output that focuses on mother tongue instruction (Heugh, 2009;Mathole, 2016) and translanguaging practices (Makalela, 2015;Probyn, 2019), which although related to EAC do not emphasise this approach. Thus, the purpose of this study is to come up with suggestions for improving the implementation of EAC by exploring the views of content subject teachers.…”
Section: The Context Of the Study: English Across The Curriculum In South Africamentioning
confidence: 99%